Bibliometric Analysis of Internationalization Strategies in Supporting MSME Business Growth in Indonesia - Lina Saptaria; Imam Mukhlis; F. Danardana Murwani (Yayasan Ilomata, 2023)
Research on MSME internationalization strategies is interesting and important in increasing global scale business growth. This study aims to analyze the five dimensions of internationalization strategy including market entry, target market strategy, time strategy, allocation strategy, and coordination strategy that supports MSME business growth in Indonesia. There have been no studies that have reviewed this topic using bibliometric analysis. Our analysis includes 180 journal articles published in Scopus, Google Scholar, and Crossref between 2018 – 2023. Researchers use VOSviewer software to classify and visualize research results. Research findings show that Indonesian MSME players combine several internationalization strategies such as market entry strategies, target market strategies, allocation strategies, and coordination strategies synergistically through e-commerce development so that they can help exploit existing competitive advantages or create new competitive advantages in the international market. Research on time strategies and allocation strategies has not been explored much, therefore this can be raised as a further research topic. The implications of this research present a bibliometric analysis of the dimensions of Indonesia's MSME internationalization strategy and propose future research directions.